Peran Pancasila dalam menumbuhkan rasa patriotisme tanah air pada generasi muda - Irhasy, Muhammad; Habibah, Siti Maizul (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The decline of patriotism in the young generation of Indonesia is a significant problem in today's society. This phenomenon is caused by the influx of various foreign cultural elements that dominate, leading many teenagers to ignore their local culture and consider foreign cultures as more modern. In this era of globalization, the spirit of patriotism and nationalism has decreased along with the weakening love for the homeland. The level of this love can be measured by the younger generation's understanding of existing cultural values. They also tend to show more interest in Western culture and choose imported goods over local products. All of this can be interpreted as a sign of declining patriotism among the young generation. Therefore, it is important to prepare the next generation to be aware of their cultural identity, receive a good education, and be able to apply the values of Pancasila. Hopefully, this next generation will have the skills, independence, and ability to develop knowledge and create a prosperous and just country in the future.